Unmasking small-bowel DLBCL in an elderly patient with simultaneous multiple primary cancers through anemia: a case report and literature review - Da, Binlin; Zhao, Chen; Yao, Yao; Dai, Chengting; Zhu, Nan; Yan, Wei; Zhang, Juanjuan; Jiang, Jun; Wang, Zhiming; Guo, Lei (Frontiers in Oncology, 2026)
Multiple primary cancers (MPC) refer to the occurrence of two or more histologically distinct tumor types in a single individual, either simultaneously or sequentially. This report presents a rare and instructive case of a 71-year-old male who developed primary small intestinal diffuse large B-cell lymphoma (DLBCL) nine years after curative treatment for synchronous cardia and lung adenocarcinomas. The patient presented with dizziness and fatigue. Initial evaluation at a local hospital revealed moderate anemia (hemoglobin 66 g/L). Esophagogastroduodenoscopy and colonoscopy showed no remarkable findings. Subsequently, capsule endoscopy was performed. The capsule endoscopy demonstrated a segment of abnormal small bowel mucosa, showing marked edema, extensive erosions, and deep ulcers. The patient was then admitted to our center for further diagnosis and treatment. Chest computed tomography (CT) demonstrated postoperative changes from the prior lung and cardia cancers. Contrast-enhanced abdominal CT revealed focal ileal wall thickening and multiple small lymph nodes, suggestive of a neoplastic lesion. Further investigation was recommended. Single-balloon enteroscopy revealed a circumferential neoplastic growth, approximately 10 cm in length, with an ulcerative appearance and a dirty purulent coating in the ileum. Biopsy of the ileal lesion revealed a malignant lymphohematopoietic tumor with ulceration and necrosis, which on immunohistochemistry supported a diagnosis of aggressive B-cell lymphoma. Then the patient completed positron emission tomography - computed tomography (PET-CT) showing primary small-bowel lymphoma, Lugano staging 1E. To alleviate anemia and reduce the tumor burden, a partial resection of the ileum was performed. The segmental ileal resection confirmed DLBCL. Postoperatively, the patient was advised to be transferred to the oncology department for R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) chemoimmunotherapy. This case highlights the diagnostic challenge of evaluating new symptoms in cancer survivors and underscores the critical importance of considering metachronous hematologic malignancies, even with atypical presentations like isolated anemia, to avoid anchoring bias towards prior solid tumors.